2017
DOI: 10.1097/qai.0000000000001363
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Continuous Quality Improvement Intervention on Retention-In-Care at 6 Months Postpartum in a PMTCT Program in Northern Nigeria: Results of a Cluster Randomized Controlled Study

Abstract: CQI as implemented in this study did not differ across study arms in the rates of retention. Several intervention design or implementation issues or other contextual constraints may explain the absence of effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(60 citation statements)
references
References 16 publications
0
60
0
Order By: Relevance
“…Most RCTs were carried out in high-income countries, with 15 in the USA [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54], two in the Netherlands [55,56], two in Canada [57,58], two in the UK [59,60], and one each in Sweden [61] and Spain [62]. Four RCTs were undertaken in the middle-or low-income countries, specifically in India [63], Mexico [64], Nigeria [65], and Malawi [66]. Another RCT was conducted across multiple African countries [67].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most RCTs were carried out in high-income countries, with 15 in the USA [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54], two in the Netherlands [55,56], two in Canada [57,58], two in the UK [59,60], and one each in Sweden [61] and Spain [62]. Four RCTs were undertaken in the middle-or low-income countries, specifically in India [63], Mexico [64], Nigeria [65], and Malawi [66]. Another RCT was conducted across multiple African countries [67].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The clinical setting for the RCTs was mainly in primary (i.e., general practice) (13 RCTs) [40, 41, 43, 44, 48-53, 58, 62, 64] or secondary care (i.e., hospitals) (10 RCTs) [45, 54, 55, 59-61, 63, 66-68]. The remaining five RCTs were set in substance misuse clinics [69], community outreach [65], social services, and social care [47,57] or tertiary care [56]. Most RCTs were published recently, with 19 RCTs published since 2010 [40, Under half of outcomes Less than half of the outcomes in studies showed a statistically significant benefit from CQI versus its comparator.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rates of retention were no different by study arm regardless of the definition used. 11 Again, the study team invested enormous effort and commitment to support local health facility teams to learn and implement CQI and the Breakthrough Series methods. 12 Facility teams enthusiastically engaged in the CQI process and actively tested change ideas—more than 41 in total across the intervention sites.…”
Section: Health Systems' Intervention and Retention In Care And Othermentioning
confidence: 99%
“…In this study, peer support and community health worker support were not statistically significant predictors of missed visits. This is not surprising since most community interventions have not been proven to improve retention in PMTCT [13].…”
Section: Discussionmentioning
confidence: 91%